Perfect Competition Market In Islamic Economic Perspective - Laila FajrinManik; Dedi Rahmad Wahyudi (Proceeding International Seminar of Islamic Studies, 2019)
Markets are important entities in economic activity. The market is a place to meet buyers and sellers. The market is a place to meet demand and supply. Adam Smith said that the companies interacting in the market seemed to have an invisible hand. IbnuTaimiyah said that Islamic markets are like perfect competition markets. For this reason, this study aims to determine the characteristics of a perfectly competitive market, find out how the market structure is in Islam, and to find out how Islam views the perfect competition market and to compare conventional concepts and Islamic concepts related to perfect competition markets. This research uses qualitative research methods. Data collection techniques used are literature and internet research. The results of this study are the invisible hand can be seen when the market structure is a perfectly competitive market. The characteristics found in the Islamic market have rules on how demand and supply affect each other. Monopolistics are banned and many make markets banned. The conclusion from the research shows that the structure and characteristics of a perfectly competitive market is an Islamic market. Ibn Taimiyah said that Islamic markets are like perfect competition markets.